Chemotherapy response evaluation using diffusion weighted MRI in Ewing Sarcoma: A single center experience. (April 2023) - Kayal, Esha Baidya; Alampally, Jayendra Tiru; Sharma, Raju; Bakhshi, Sameer; Mehndiratta, Amit; Kumar, Rakesh; Chandrashekhara, SH; Jana, Manisha; Bhalla, Ashu Seith; Sharma, Mehar Chand; Mridha, Asit Ranjan; Vishnubhatla, Sreenivas; et al.
Background: Non-invasive biomarkers for early chemotherapeutic response in Ewing sarcoma family of tumors (ESFT) are useful for optimizing existing treatment protocol. Purpose: To assess the role of diffusion-weighted magnetic resonance imaging (MRI) in the early evaluation of chemotherapeutic response in ESFT. Material and Methods: A total of 28 patients (mean age = 17.2 ± 5.6 years) with biopsy proven ESFT were analyzed prospectively. Patients underwent MRI acquisition on a 1.5-T scanner at three time points: before starting neoadjuvant chemotherapy (baseline), after first cycle chemotherapy (early time point), and after completion of chemotherapy (last time point). RECIST 1.1 criteria was used to evaluate the response to chemotherapy and patients were categorized as responders (complete and partial response) and non-responders (stable and progressive disease). Tumor diameter, absolute apparent diffusion coefficient (ADC), and normalized ADC (nADC) values in the tumor were measured. Baseline parameters and relative percentage change of parameters after first cycle chemotherapy were assessed for early detection of chemotherapy response. Results: The responder:non-responder ratio was 21:7. At baseline, ADC ([0.864 ± 0.266 vs. 0.977 ± 0.246]) × 10 −3 mm 2 /s; P  = 0.205) and nADC ([0.740 ± 0.254 vs. 0.925 ± 0.262] × 10 −3 mm 2 /s; P  = 0.033) among responders was lower than the non-responders and predicted response to chemotherapy with AUCs of 0.6 and 0.735, respectively. At the early time point, tumor diameter (27% ± 14% vs. 4.6% ± 10%; P  = 0.002) showed a higher reduction and ADC (75% ± 44% vs. 52% ± 72%; P  = 0.039) and nADC (81% ± 44% vs. 48% ± 67%; P  = 0.008) showed a higher increase in mean values among responders than the non-responders and identified chemotherapy response with AUC of 0.890, 0.723, and 0.756, respectively. Conclusion: Baseline nADC and its change after the first cycle of chemotherapy can be used as non-invasive surrogate markers of early chemotherapeutic response in patients with ESFT.